Ascaris lumbricoides and Ascaris suum: A comparison of electrophoretic banding patterns of protein extracts from the reproductive organs and body wall - Alba, Julisar Elaine (Animo Repository, 2009)
Ascaris lumbricoides and Ascaris suum were analysed for similarities and differences in the banding patterns of proteins extracted from the body wall (BW) and reproductive organs (ROS). Ascaris lumbricoides and a. suum manifested considerable similarity in protein profile. The BW of female ascarids manifested 10 common bands, while males had 12 common bands, and of these proteins, at least five were common to both sexes. A comparison of the ROS banding profile between female and male Ascaris lumbricodes and A. suum revealed 11 and 12 common bands, respectively, of which six bands were shared. While the BW and ROS of male ascarids revealed eight shared bands, female ascarids had only two common bands. The detection of 25 kDa, 20-21 kDa and 18 kDa bands in virtually all protein samples assayed suggests their importance as housekeeping molecules and possibly valuable markers. The appreciable similarities in protein banding patterns between human and hog ascarids reflect their close genetic relationship. In view of current findings and earlier documented studies pointing to the zoonotic nature and high probability of cross-infection between human and hog species, control strategies should take into consideration the simultaneous deworming of infected persons and hogs. The likelihood of cross-infection between human and hog Ascaris spp. in the country can be further assessed through surveillance of human and hog ascarids, in places where backyard hog-rearing is still commonly practised. The current electrophoretic protein profiling of Ascaris spp. is the first of its kind in the country.